Investigating social gaze as an action-perception online performance - Grynszpan, Ouriel; Simonin, Jérôme; Martin, Jean-Claude; Nadel, Jacqueline (Frontiers in Human Neuroscience, 2012)
Gaze represents a major non-verbal communication channel in social interactions. In this respect, when facing another person, one's gaze should not be examined as a purely perceptive process but also as an action-perception online performance. However, little is known about processes involved in the real-time self-regulation of social gaze. The present study investigates the impact of a gaze-contingent viewing window on fixation patterns and the awareness of being the agent moving the window. In face-to-face scenarios played by a virtual human character, the task for the 18 adult participants was to interpret an equivocal sentence which could be disambiguated by examining the emotional expressions of the character speaking. The virtual character was embedded in naturalistic backgrounds to enhance realism. Eye-tracking data showed that the viewing window induced changes in gaze behavior, notably longer visual fixations. Notwithstanding, only half of the participants ascribed the window displacements to their eye movements. These participants also spent more time looking at the eyes and mouth regions of the virtual human character. The outcomes of the study highlight the dissociation between non-volitional gaze adaptation and the self-ascription of agency. Such dissociation provides support for a two-step account of the sense of agency composed of pre-noetic monitoring mechanisms and reflexive processes, linked by bottom-up and top-down processes. We comment upon these results, which illustrate the relevance of our method for studying online social cognition, in particular concerning autism spectrum disorders (ASD) where the poor pragmatic understanding of oral speech is considered linked to visual peculiarities that impede facial exploration.